How high is too high? Challenges on the next generation of dewatered tailings stacks - Norambuena Mardones, R.E.; Caldwell-Crystal, C.; Cobos, D. (Paste 2023: Proceedings of the 25th International Conference on Paste, Thickened and Filtered Tailings, 2023)
Building on the experience of successful smaller-scale dewatered tailings stack operations with production rates of up to 35,000 tpd, filter-pressed tailings stacking is being considered as a technically and economically viable alternative of dewatered tailings management for even higher production rates, pushing 50,000 to 100,000 tpd, involving intensive earthworks operations and intricate construction sequencing plans. The need to establish dewatered tailings solutions as a sound business option for large-scale projects in water-stressed nations like Chile and Mexico is motivated by water (the lack of availability, rising cost of water and sustainable water use) but also by dam safety, lowering the risk profile of the large conventional tailings storage facility portfolios. This paper will present the fundamental aspects of the design and operation of dewatered stacks based on practical planning and operational experience. This will ultimately provide some guidance on "how high is too high?" in the context of critical state soil mechanics and other relevant geotechnical aspects and a case study providing some reference on the planning of a dewatered stack.